Effects of Dietary Protein Levels on Production Performance, Meat Quality Traits, and Gut Microbiome of Fatting Dezhou Donkeys - Yunpeng Wang; Keqiang Diao; Han Li; Chongyu Zhang; Guiguo Zhang; Cuihua Guo (Microorganisms, 2025)
This study aimed to investigate the effects of varying dietary protein levels on growth performance, meat quality traits, amino acid and fatty acid compositions, and hindgut microbiota in Dezhou donkeys. Eighteen 12-month-old male donkeys, weighing 188 ± 9 kg, were randomly allocated into three groups and fed diets containing 11.03% (LP), 12.52% (MP), and 14.06% (HP) protein. The average daily gain (ADG) was significantly higher (p < 0.05) in the HP and MP groups, while the feed conversion ratio (FCR) was lower (p < 0.05) compared to the LP group. The MP group exhibited superior performance in terms of serum albumin (ALB) and high-density lipoprotein (HDL) levels, as well as protein digestibility (p < 0.05). Improvements in meat tenderness, as well as increased levels of leucine, flavor amino acids (FAAs), and non-essential amino acids (NEAAs) (p < 0.05), were observed in the MP group compared to those in the LP and HP groups. The levels of total fatty acids (TFAs), saturated fatty acids (SFAs), unsaturated fatty acids (UFAs), and monounsaturated fatty acids (MUFAs) were higher (p < 0.05) in the LP and MP groups than in the HP group, with no significant differences (p > 0.05) observed between the LP and MP groups. The genera Prevotella, Clostridium_sensu_stricto_1, NK4A214_group, Oscillospiraceae_UCG-002, and Oscillospiraceae_UCG-005 in the rectum were identified as differential microbes associated with varying dietary protein levels. In conclusion, this study indicates that a dietary protein level of 12.52% could enhance the growth performance, dietary nutrient digestibility, slaughter performance, and meat quality of Dezhou donkeys by modulating hindgut microbial communities.